Methodological Bases of Formation of the Socioeconomic and Environmental Constraints Ownership of Natural Recreation and Tourism Resources (Economic journal of Lesya Ukrainka Volyn National University, 2016)
It is proved that the essence of the concept of economic and environmental constraints form of ownership of natural recreation and tourism resources lies in the fact that regardless of the form of ownership of the natural resources of the subject property can not pollute and deplete natural object above the allowable standards, it is obliged to apply certain environmentally friendly ways to use, extraction and processing of resources, the use of renewable technologies, etc. competences Restrictions may also be (depending on the specificity of the natural resources) is that you can not sell the natural resources without the permission of the state, can not take the natural resource rent without the permission of the state, can not be used in a manner detrimental toother natural objects and property of other subjects. Preconditions of formation of the socioeconomic and environmental constraints and the basic directions of their introduction. It is proved that limits should take into account the interests of the whole people of appropriation of natural resources and, depending on the specific characteristics of the natural resource recreation and tourism, as well as the directions of use restrictions are formed in the forms and property rights.
Keywords: socioeconomic and Environmental limitations, forms and property rights, nature tourist resources, priority of national property.